2020
DOI: 10.1108/jedt-06-2020-0255
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming sustainable development goals in Ghana’s energy sector within the framework of public–private partnerships: challenges, opportunities and strategies

Abstract: Purpose This paper is anchored in a premise of a universal call to action by all UN member states in 2015 to end poverty, protect the planet and ensure that all people enjoy peace and prosperity by 2030 within the blueprint of the sustainable development goals (SDGS). The purpose of this study is to mainstream the SDGs in Ghana’s energy sector within the framework of public–private partnerships (PPP): challenges, opportunities and strategies. Design/methodology/approach Literature review was carried out to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…The findings revealed that although the companies are to some extent delivery on their mandate of social responsibilities there is still much to be done. The results also affirm the assertion made by Mezher et al (2010), Owusu-Manu et al (2021a and Kukah et al (2021) that not only new companies are tied to social responsibilities but also the old companies are also effortlessly involved in the practice of CSR. The outcomes also revealed that although the country had no CSR policy for energy supply companies to follow and not being compelled to see to the development of the communities where they operate, the companies were fulfilling and meeting to some extent the development needs of the communities.…”
Section: 50 Discussionsupporting
confidence: 88%
“…The findings revealed that although the companies are to some extent delivery on their mandate of social responsibilities there is still much to be done. The results also affirm the assertion made by Mezher et al (2010), Owusu-Manu et al (2021a and Kukah et al (2021) that not only new companies are tied to social responsibilities but also the old companies are also effortlessly involved in the practice of CSR. The outcomes also revealed that although the country had no CSR policy for energy supply companies to follow and not being compelled to see to the development of the communities where they operate, the companies were fulfilling and meeting to some extent the development needs of the communities.…”
Section: 50 Discussionsupporting
confidence: 88%
“…Besides, PPP can also be seen as new business prospects for the private parties to invest and profit. Hence, private sectors may have the ability to improve their sustainable economic development by undertaking PPP projects (Owusu-Manu et al, 2020). On the other hand, social welfare should be protected when developing concession agreements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PPP-led infrastructure development projects should address all these critical obstacles to achieve the economic, social and environmental efficiency that could lead to the growth of the industry. Further, new policies that incorporate business opportunities such as carbon trading will enhance sustainability [30]. Overcoming the key obstacles will help achieve sustainability, and a sustainability-led project evaluation would facilitate efficiency in PPP-led infrastructure development, together bringing better outcomes and greater sustainability.…”
Section: Discussionmentioning
confidence: 99%